The Role of Dietary Fatty Acids in Modulating Blue Crab (Callinectes sapidus) Physiology, Reproduction, and Quality Traits in Captivity - Federico Conti; Lina Fernanda Pulido-Rodriguez; Giulia Chemello; Nico Cattaneo; Mattia Resente; Giuliana Parisi; Ike Olivotto; Matteo Zarantoniello (Animals)
The invasive blue crab is challenging the Mediterranean basin, progressively declining local populations. This reflects a lower prey availability and suitability of dietary nutrients (mainly n-3 polyunsaturated fatty acids, PUFA). The present study aimed to challenge blue crab males and females with a feed source low in n-3 PUFA with respect to one showing a proper fatty acid profile and to investigate the responses in terms of growth, welfare, lipid characterization of target tissues, and reproductive status. Blue crabs were divided into three groups as follows: (i) Marine: crabs fed sardinella (Sardinella aurita) fillet for 60 days; (ii) Mix: crabs fed bovine heart for the first 40 days and sardinella fillet for the following 20 days; and (iii) Terrestrial: crabs fed bovine heart for 60 days. The diet did not alter the health status but reflected the fatty acid profile of muscle and ovary of the blue crabs. In each group, males and females showed a proper hepatopancreas structure, with comparable levels of lipid reserves. This properly supported gonad maturation in both sexes. However, males and females from the group fed the terrestrial diet were characterized by reduced body weight, revealing that blue crabs prioritize reproductive investment rather than growth by directing crucial nutrients to reproductive organs when a suboptimal diet is available.